IN SILICO MOLECULAR PROPERTIES PREDICTION OF COMPOUNDS FROM CARICA PAPAYA LEAF EXTRACT - NARA, ABHIGNA; BL, KUDAGI; KR, SUBASH; RAYAM, SRIHARSHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objectives of the study were to analyze the scientific rationale and possible pharmacokinetic properties of certain biologically active compounds from Carica papaya leaf extract in silico. Methods: This study was investigated on web-based tools PUBCHEM to extract the chemical structure followed by authentication and validation with chemical formula. The 2-dimensional structures are further converted to 3-dimensional (3D) structure with CHEMSKETCH software, the derived 3D structures are then screened for molecular properties and druglikeness score followed by absorption, distribution, metabolism, elimination, and toxicity through admetSAR software. The reports are analyzed and predicted for possible drug like compound in leaf extract of papaya. Results: The results obtained indicate that the compounds screened papain, chymopapain, quercetin, and protocatechuic acid had the druglikeness score −0.93, −0.05, + 0.93, and +0.74, respectively. On acute toxicity prediction, quercetin belonged to Class II and other compounds belonged to Class III. Conclusion: The study confirms the among the compounds screened for in silico druglikeness and adsorption, distribution, metabolism, excretion, and toxicity profile quercetin a flavonoid can be possibly developed as effective anti-dengue compound.